Pengaruh Program Pelatihan Ketrampilan dan Pembinaan Dinas Koperasi dan Usaha Mikro terhadap Perkembangan Usaha Mikro di Kabupaten Blitar - Feri Bagus Setiawan (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2023)
This research is motivated by the phenomenon of the increasing number of entrepreneurial people, especially in Blitar Regency. Basically, the existence of this phenomenon will bring a positive influence on the economy of society and the country. Therefore, the government, namely the Office of Cooperatives and Micro Enterprises, took part in it by conducting training and coaching programs. In this training program, the priority is the management of its own human resources. This research will examine the influence of the training program provided by the government on the development of local MSMEs, especially in Blitar Regency. The approach used is a quantitative approach and is field. The data collected, namely primary and secondary, will be in the form of a questionnaire and processed using SPSS with a Likert Scale as a measure. The results of this study indicate that training and guidance from the government have a positive effect on the development of micro-enterprises. Training has a big impact on people who are going to or are starting a business, because the training provided by the relevant agencies is very helpful in implementing entrepreneurship and its development, as well as coaching, people feel more nurtured and directed in building and managing the business being run.